The Role of Craftsmen Group in Increasing Potential Tourism of Paksebali Village - Farhaeni, Mutria; Prami, Anak Agung Istri Ngurah Dyah; Martini, Sri (ETNOSIA : Jurnal Etnografi Indonesia, 2024)
By exploiting the potential of art and culture that exists in Paksebali Village, this can be a prominent and sustainable tourist destination. The synergy between the craftsmen group and the tourism sector will not only boost the local economy, but also ensure that this rich cultural heritage is preserved and appreciated by future generations. Innovation in craft products that combines local cultural elements with modern trends. While previous research mostly deals with Although previous research mostly discussed the tourism potential in Paksebali Village, this article focuses on craftsmen who can create various types of products that are attractive to tourists, such as Endek Cloth Weaving Craft, Tedung, Prada Bludru Craft, Lontek Craft, Gambelan Bali Craft, Topeng Bali Craft. This diversification helps attract tourists who have a variety of preferences. This qualitative research was conducted in Paksebali village, Dawan Subdistrict, Klungkung Regency, Bali. Data was collected using the combination between in-depth interview and  observations. The informants who participated in this research are craftsmen in Paksebali village, as my case studies. The findings show that through synergies between the craftsmen group and the tourism sector, there is a mutually beneficial exchange of value. Tourists gain experience and quality products, while the craftsmen gain the opportunity to increase their income and expand their market. In addition to economic benefits, these collaborations also have an impact on the preservation of local culture. Craftsmen products often reflect the history, tradition, and identity of a region. With increasing tourist interest in these products, the group of craftsmen is encouraged to continue to preserve and develop their expertise. Craftsmen in Paksebali Village can help increase the village's attractiveness as a tourist destination, while maintaining and preserving local cultural heritage. It is recommended that Craftsmen in Paksebali Village is expected to improve quality and innovation in craft products, setting up a craft centre or gallery, working with tourism agencies, conducting digital marketing and promotion, improving the packaging of craft products to make them more attractive, actively participating in exhibitions and festivals as well as cultural preservation and education.